Neuronal Nav1.8 Channels as a Novel Therapeutic Target of Acute Atrial Fibrillation Prevention. Issue 11 (2nd November 2016) - Chen, XiaoMeng; Yu, LiLei; Shi, ShaoBo; Jiang, Hong; Huang, CongXin; Desai, Mayurika; Li, YiGang; Barajas‐Martinez, Hector; Hu, Dan
Abstract : Background: Ganglionated plexus have been developed as additional ablation targets to improve the outcome of atrial fibrillation (AF) besides pulmonary vein isolation. Recent studies implicated an intimate relationship between neuronal sodium channel Nav 1.8 (encoded by SCN10A ) and AF. The underlying mechanism between Nav 1.8 and AF remains unclear. This study aimed to determine the role of Nav 1.8 in cardiac electrophysiology in an acute AF model and explore possible therapeutic targets. Methods and Results: Immunohistochemical study was used on canine cardiac ganglionated plexus. Both Nav 1.5 and Nav 1.8 were expressed in ganglionated plexus with canonical neuronal markers. Sixteen canines were randomly administered either saline or the Nav 1.8 blocker A‐803467. Electrophysiological study was compared between the 2 groups before and after 6‐hour rapid atrial pacing. Compared with the control group, administration of A‐803467 decreased the incidence of AF (87.5% versus 25.0%, P <0.05), shortened AF duration, and prolonged AF cycle length. A‐803467 also significantly suppressed the decrease in the effective refractory period and the increase in effective refractory period dispersion and cumulative window of vulnerability caused by rapid atrial pacing in all recording sites. Patch clamp study was performed under 100 nmol/L A‐803467 in TSA201 cells cotransfected with SCN10A ‐WT, SCN5A ‐WT, and SCN3B ‐WT. IN a, P was reduced by 45.34% at −35 mV, and IN a, L by 68.57% at −20 mV. Evident fast inactivation, slow recovery, and use‐dependent block were also discovered after applying the drug. Conclusions: Our study demonstrates that Nav 1.8 could exert its effect on electrophysiological characteristics through cardiac ganglionated plexus. It indicates that Nav 1.8 is a novel target in understanding cardiac electrophysiology and SCN10A ‐related arrhythmias.